Decomposition Characterizations of Methane Hydrate Confined inside Nanoscale Pores of Silica Gel below 273.15 K - Wan, Lihua; Zhou, Xuebing; Chen, Peili; Zang, Xiaoya; Liang, Deqing; Guan, Jinan (Crystals, 2019)
The formation and decomposition of gas hydrates in nanoscale sediments can simulate the accumulation and mining process of hydrates. This paper investigates the Raman spectra of water confined inside the nanoscale pores of silica gel, the decomposition characterizations of methane hydrate that formed from the pore water, and the intrinsic relationship between them. The results show that pore water has stronger hydrogen bonds between the pore water molecules at both 293 K and 223 K. The structure of pore water is conducive to the nucleation of gas hydrate. Below 273.15 K, the decomposition of methane hydrate formed from pore water was investigated at atmospheric pressure and at a constant volume vessel. We show that the decomposition of methane hydrate is accompanied by a reformation of the hydrate phase: The lower the decomposition temperature, the more times the reformation behavior occurs. The higher pre-decomposition pressure that the silica gel is under before decomposition is more favorable to reformation. Thus, reformation is the main factor in methane hydrate decomposition in nanoscale pores below 273.15 K and is attributed to the structure of pore water. Our results provide experimental data for exploring the control mechanism of hydrate accumulation and mining.